Dark citations to Federal resources and their contribution to the public health literature - Keralis, Jessica M.; Albertorio-Díaz, Juan; Hoppe, Travis (Frontiers in Research Metrics and Analytics, 2023)
The term “dark citations,” which has been previously used to refer to citations of information products outside of traditional peer-reviewed journal articles, is adapted here to refer to those that are not linked to a known indexed identifier and are effectively invisible to traditional bibliometric analysis. We investigate an unexplored source of citations in the biomedical and public health literature by surveying the extent of dark citations across the U.S. government. We systematically focus on public health, quantify their occurrences across the government, and provide a comprehensive dataset for all dark citations within PubMed.